Presenting a Model of Psychological Vulnerability Based on Alexithymia in Multiple Sclerosis Patients: The Mediating Role of Anxious Thoughts - Salimi, Laleh; Zarbakhsh Bahri, Mohammadreza; Pirkhaefi, Alireza (Health Nexus, 2024)
Among the stress-inducing events that impact an individual’s psychological well-being, chronic illnesses such as multiple sclerosis (MS) are significant. These patients not only face physical challenges but also encounter numerous psychological issues that further exacerbate their illness and contribute to their psychological vulnerability. The current study aimed to determine the indirect effect of Alexithymia on the psychological vulnerability of MS patients, mediated by anxious thoughts. The study method was descriptive-correlational. The population consisted of members of the MS Society of Tehran in 2022. A total of 312 patients were selected using convenience sampling (n = 312). Data collection tools included the Toronto Alexithymia Scale (Bagby, Parker, & Taylor, 1994), the 25-Item Symptoms Checklist by Nejarian and Davoudi (2001), and the Wells Anxious Thoughts Questionnaire (1994). Data analysis using structural equation modeling indicated that the model of psychological vulnerability based on Alexithymia with the mediating role of anxious thoughts fits well. Also, the effect of Alexithymia on psychological vulnerability (β = 0.371; p < 0.001), the effect of anxious thoughts on psychological vulnerability (β = 0.463; p < 0.001), and the effect of Alexithymia on anxious thoughts (β = 0.367; p < 0.001) were positive and significant. The findings of this study could guide the development of comprehensive therapeutic models for patients with MS and their emotional issues.